Reviewed Study on Indian Pension Reform and Indian Pension Reform: Understanding the Impact of British Rule on Indian Labor Legislation and the Importance of Pension Reform (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The history of labor legislation in India is interwoven with the history of British rule in India. Initially, labor or industrial legislation was developed to protect the interest of British companies and employers. It is obvious that the British political economy was naturally paramount in developing most of the legislation related to laborers, employees, and organizations during the British rule. In developing countries like India, social security is important as it typically evokes the notion of a complete framework of public policy including several welfare elements like food security for all, healthcare for every citizen, availability of drinking water and sanitation, land distribution, education for all, social insurance, and skill development. An employee who has invested vital period of his life in the service in an organization, a retirement benefit or retirement plan in any form is not just a reward for the service he rendered till the last day of his retirement but it bears more importance in his life. A retirement plan is a socio-economic measure whereby a person gets economic security at the time when he is no more physically and mentally prudent to lead an active life. A retired employee gets a recurring monthly payment for life and a lump sum amount at the time of retirement that is known as gratuity. Both of the benefits are fixed on the basis of his position in the organization, length of his service, and the salary last is drawn. The term “pension” has been legally defined as a stated allowance or stipend fixed for an employee. The non-payment of the same is the infringement of an individual’s fundamental right under Article 21 of the Constitution of India. Thus, whenever such infringement occurs, the affected employee can seek the help of the judicial system of the country and unless there is any strong ground court does not tolerate such infringement.